Downward Longwave Irradiance at the Thule High Arctic Atmospheric Observatory during MACMAP (THAAO_DLI_MACMAP) - Meloni, Daniela; Di Sarra, Alcide; Pace, Giandomenico; Di Iorio, Tatiana; Muscari, Giovanni; Iaccarino, Antonio; Calì Quaglia, Filippo (Agenzia Nazionale per le nuove tecnologie, l’energia e lo sviluppo economico sostenibile (ENEA), 2021)
Measurements of downward shortwave (SW) and longwave (LW) irradiance are collected by Kipp&Zonen CMP21 pyranometer and CGR4 pyrgeometer, respectively, installed on the roof of building 1971. Both sensors are ventilated to prevent ice formation on their domes. Data are recorded at 1 minute time step. Corrections are applied to measurements in order to take into account the dependance of the radiometers’ sensitivity on temperature and the change in time. The small pyranometer's thermal offset is also corrected.
Approximately 100 m away from the building, Eppley pyranometer and pyrgeometer are installed facing the surface at about 2.3 m agl to measure upward SW and LW irradiance, respectively. These radiometers are not ventilated. Irradiances, as well as the radiometers’ tilt with respect to the horizontal, are collected at time steps of 30 seconds.
The production of these data sets is also funded by the Environment Department of INGV through the MACMAP project.
THAAO_DLI_MACMAP
Keywords: climate change; Arctic amplification; surface radiative balance; cloud radiative effect